A comparative study on using superior thyroid artery perforator flaps versus traditional sternocleidomastoid myocutaneous flaps for reconstructions after oral cancer ablation: "New tricks for old dogs"?. (October 2021) - Ma, Chunyue; Sheng, Surui; Shen, Yi; Gao, Weijin; Haugen, Thorsen; Wang, Liang; Sun, Jian
Abstract: Objectives: To introduce new superior thyroid artery perforator flaps (STAPF), and to compare the clinical outcomes with sternocleidomastoid myocutaneous flaps (SCMMF) for their intraoral applications. Materials and methods: Between January 2013 and December 2020, forty-three oral cancer patients who received post-oncologic reconstructions with one of these two regional flaps were retrospectively collected. Their techniques and outcomes were compared. All the STAPFs were preprepared with radiologic evaluations. Results: Despite the common arterial origins, the compositions and harvesting procedures of STAPF and SCMMF were different. Though SCMMFs (n = 23) were designed in rotational styles, most STAPFs (n = 20) were septocutaneous perforator flaps, with 2 chimeric ones. In addition, the sizes of STAPFs were generally larger than those of SCMMFs ( p  = 0.006). Success rate for STAPFs was much higher, with only three partial cutaneous necroses. Radiotherapy delay was more frequently found in those reconstructed with SCMMFs ( P  = 0.046), mostly due to fistula formations. Besides, incomplete level IIB dissections were also reported in 9 (20.9%) patients in SCMMF group. In our study, the overall survival was affected by both flap conditions ( p  = 0.014, 1.333–12.881) and postoperative surgical complications (except fistula) ( P  = 0.005, 2.240–84.134). Functionally speaking, post-reconstructive speech and neck mobility ( p  < 0.001) were better in the STAPF group. Conclusions: With accumulated experiences on the use of locoregional flaps in the neck, STAPF, when well-prepared, can provide superior reconstructive outcomes for various intraoral defects. As a comparison with SCMMF in the same middle region, STAPF is a viable option with higher success rates and oncological safety for oral cancer patients.